A pilot randomised clinical trial of mepolizumab in COPD with eosinophilic bronchitis. Issue 3 (16th March 2017) - Dasgupta, Angira; Kjarsgaard, Melanie; Capaldi, Dante; Radford, Katherine; Aleman, Fernando; Boylan, Colm; Altman, Leonard C.; Wight, Thomas N.; Parraga, Grace; O'Byrne, Paul M.; Nair, Parameswaran
Airflow limitation in chronic obstructive pulmonary disease (COPD) is associated with influx of various inflammatory cells ( e.g. eosinophils, neutrophils, lymphocytes, macrophages) into the airways. Approximately one-third of stable COPD patients and one in five COPD exacerbations are associated with eosinophilic bronchitis that usually responds to inhaled or ingested corticosteroids [1]. Specific anti-eosinophil agents like mepolizumab, a humanised monoclonal antibody against interleukin 5 (IL-5), reduce severe asthma exacerbations and improve lung function [2–4]. The improvement in forced expiratory volume in 1 s (FEV1 ) is also associated with a decrease in biomarkers of airway remodelling, such as sputum hyaluronan and versican, over a 6-month treatment period [5]. It is not known if the same benefits are observed in patients with COPD and eosinophilia in whom the airflow obstruction is due to cigarette smoke-related bronchitis and emphysema. Eosinophils may not directly contribute to luminal obstruction in COPD although they may predict steroid response http://ow.ly/b3Au308wA0m